2008
DOI: 10.1159/000155137
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin N-Terminal Peptide Causes Catabolic Effects via the Hypothalamus and Prostaglandin-Dependent Pathways

Abstract: Recent evidence suggests that the free amino-terminal fragment of procalcitonin (N-PCT) plays a role in the central control of feeding behavior and energy homeostasis. However, little is known about the mechanisms through which N-PCT works. Here we report that intracerebroventricular administration of N-PCT to free-feeding male rats induced a significant decrease of longer-term food intake and body weight gain. Conversely, N-PCT increased body temperature. We also show that intracerebroventricular administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 98 publications
4
24
0
1
Order By: Relevance
“…N-PCT-immunoreactive fibers and cells have been observed in several areas of the adult rat brain but are found the in highest concentrations in appetite control hypothalamic nuclei expressing high density of CT-R, including the ARC and PVN (4,34,37,54,57). In the present study, we found that N-PCT is produced locally within the ARC, including within POMC neurons, astrocytes, and possibly other neurons.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…N-PCT-immunoreactive fibers and cells have been observed in several areas of the adult rat brain but are found the in highest concentrations in appetite control hypothalamic nuclei expressing high density of CT-R, including the ARC and PVN (4,34,37,54,57). In the present study, we found that N-PCT is produced locally within the ARC, including within POMC neurons, astrocytes, and possibly other neurons.…”
Section: Discussionsupporting
confidence: 60%
“…To characterize cell types expressing N-PCT, hypothalamic sections were subjected to double-labeling immunohistochemistry for a neuronal nuclei (NeuN) or a glial marker [glial fibrillary acidic protein (GFAP)], as described previously (54). To determine whether POMC neurons express N-PCT, double-labeling immunohistochemistry was performed using a rabbit anti-POMC antibody (57). Briefly, after quenching of autofluorescence with 0.3 M glycine and saturation of nonspecific sites with 3% normal donkey serum (Jackson Laboratories, West Grove, CA), sections were incubated for 72 h at 4°C with a mouse anti-N-PCT monoclonal antibody (1:100; Abcam) or incubated overnight at 4°C with rabbit anti-NeuN antibody (1:500; Millipore), anti-GFAP antibody (1:500; Dakocytomation, Carpinteria, CA), or anti-POMC antibody (1:1,000; Phoenix Pharmaceuticals).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations